Settlers, target-earners, young professionals. Distinct migrant types, distinct integration trajectories? - Franziska Spanner; Claudia Diehl (International Migration, 2021)
In this article, we start out from theoretical concepts about different types of migrants that feature prominently in the immigration literature. By applying latent class analysis to a unique `mini-panel' data set on recent Polish and Turkish immigrants in Germany, we identify two types of migrants that are in line with the literature, namely settlers and target-earners. We label a third group that is best described as educational target-earners: `young learners/professionals'. Regarding variation in these groups' early sociocultural integration patterns, results suggest that they reflect primarily differences in migrants' intention to stay, individual resources such as education, and opportunities for integration related to newcomers' involvement in the educational system or labour force. In sum, migrant types – though certainly more intuitively appealing and vivid than single `variables' – seem to have limited explanatory power when it comes to predicting newcomers' early integration trajectories.
Keywords: 300